Entre expectativas y realidades: un análisis de los resultados del examen Saber 11 en municipios PDET y no PDET durante el año 2013. (2025)
This paper presents the results of a research on the gaps in student expectations and their performance on the Saber 11 test, comparing PDET and non-PDET municipalities. Using a quantitative analysis with multiple regression, the obtained and expected scores were examined, as well as other variables that could significantly influence performance on the test. The findings reveal that socioeconomic conditions, such as parents' educational level, material conditions, and family income, have a considerable impact on students' expectations, which in turn affects their results on the assessment.